MODELING PROCESS OF DISTRIBUTION OF LIGHT FLOW IN THE ENVIRONMENT WITH DIFFUSING CENTERS - S.S. Rybina; S.A. Tretyakov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2019)
A mathematical model is developed for calculating parameters of light fluxes propagating through a light-scattering and absorbing medium. Single crystals of paratellurite and germanium with known optical parameters and densities of various absorbing and scattering inhomogeneities were chosen as mediums.